Ultracold molecules for quantum simulation: rotational coherences in CaF and RbCs - Blackmore, JA; Caldwell, L; Gregory, PD; Bridge, EM; Sawant, R; Aldegunde, J; Mur-Petit, J; Jaksch, D; Hutson, JM; Sauer, BE; Tarbutt, MR; Cornish, SL (IOP Publishing, 2018)
Polar molecules offer a new platform for quantum simulation of systems with long-range interactions, based on the electrostatic interaction between their electric dipole moments. Here, we report the development of coherent quantum state control using microwave fields in $^{40}$Ca$^{19}$F and $^{87}$Rb$^{133}$Cs molecules, a crucial ingredient for many quantum simulation applications. We perform Ramsey interferometry measurements with fringe spacings of $\sim 1~\rm kHz$ and investigate the dephasing time of a superposition of $N=0$ and $N=1$ rotational states when the molecules are confined. For both molecules, we show that a judicious choice of molecular hyperfine states minimises the impact of spatially varying transition-frequency shifts across the trap. For magnetically trapped $^{40}$Ca$^{19}$F we use a magnetically insensitive transition and observe a coherence time of 0.61(3)~ms. For optically trapped $^{87}$Rb$^{133}$Cs we exploit an avoided crossing in the AC Stark shifts and observe a maximum coherence time of 0.75(6)~ms.